IMPROVING STUDENTS' INTERPERSONAL COMMUNICATION SKILLS USING GROUP GUIDANCE SERVICES WITH THE SOCIODRAMA TECHNIQUE - Rosana Dwi Septine; Edris Zamroni; Sucipto Sucipto (LP2M IAI Al-Khairat Pamekasan, 2026)
This research is motivated by the importance of interpersonal communication skills in students' social lives, especially at SMA N 1 Jepara, where some students still experience communication difficulties due to low self-confidence, nervousness, and a tendency to withdraw from social interactions. These problems are closely related to parenting styles and self-confidence development. This study aims to describe the implementation and effectiveness of group guidance services using sociodrama techniques to improve students' interpersonal communication skills. This study uses a quantitative approach with a quasi-experimental design of a non-equivalent control group type. The study participants were students from class X1.1 of SMA N 1 Jepara, who were selected through purposive sampling. Data were collected through Likert scale questionnaires and interviews, while data analysis was conducted using the Wilcoxon Signed Rank Test. The results of the study indicate that group guidance services using sociodrama techniques are effective in improving students' interpersonal communication skills. Through role-playing and dramatization of real social situations, students become more open, empathetic, and confident in expressing their thoughts and engaging in interactions. Therefore, sociodrama can be considered an effective alternative technique in group guidance to develop students' interpersonal communication skills.